Transient rheology of the oceanic asthenosphere following the 2012 Indian Ocean Earthquake inferred from geodetic data. (1st October 2017) - Pratama, Cecep; Ito, Takeo; Sasajima, Ryohei; Tabei, Takao; Kimata, Fumiaki; Gunawan, Endra; Ohta, Yusaku; Yamashina, Tadashi; Ismail, Nazli; Nurdin, Irwandi; Sugiyanto, Didik; Muksin, Umar; et al.
Graphical abstract: Highlights: Middle field GNSS data exhibited transient motion. The mechanism combined burgers viscoelastic relaxation and afterslip. Lithosphere thickness has a significant role on the rheological structures. Abstract: Postseismic motion in the middle-field (100–500 km from the epicenter) geodetic data resulting from the 2012 Indian Ocean earthquake exhibited rapid change during the two months following the rupture. This pattern probably indicates multiple postseismic deformation mechanisms and might have been controlled by transient rheology. Therefore, the relative contribution of transient rheology in the oceanic asthenosphere and afterslip in the oceanic lithosphere should be incorporated to explain short- and long-term transitional features of postseismic signals. In this study, using two years of post-earthquake geodetic data from northern Sumatra, a three-dimensional spherical-earth finite-element model was constructed based on a heterogeneous structure and incorporating transient rheology. A rheology model combined with stress-driven afterslip was estimated. Our best-fit model suggests an oceanic lithosphere thickness of 75 km with oceanic asthenosphere viscosity values of 1 × 10 17 Pa s and 2 × 10 18 Pa s for the Kelvin and Maxwell viscosity models, respectively. The model results indicate that horizontal landward motion and vertical uplift in northern Sumatra require viscoelastic relaxation of the oceanic asthenosphere coupled with afterslip in the lithosphere. The present study demonstrates that transient rheology is essential for reproducing the rapidly changing motion of postseismic deformation in the middle-field area.